Enhanced Magnetic Component in Synthetic Goethite (α‐FeOOH) and its Relation with Morphological and Structural Characteristics. Issue 11 (13th June 2019) - Valezi, Daniel F.; Baú, João P. T.; Zaia, Dimas A. M.; Costa, Antônio C. S.; Urbano, Alexandre; Tupan, Lilian F. S.; Paesano, Andrea; Piccinato, Marilene T.; Di Mauro, Eduardo
Abstract : Goethite (α‐FeOOH) is by definition an antiferromagnetic (AFM) material. In the present work an investigation of the magnetic properties of goethite is performed, studying the magnetic component of this material in different samples and relating these properties with its structural and morphological characteristics. Samples are synthetized in two distinct ways in order to generate solids with different degrees of structural defects and imperfections. Electron spin resonance (ESR) data show that the sample synthesized in a faster procedure, most susceptible to defects and imperfections (GC sample), shows an area under the ESR line ≈20 times higher than the sample set for a lower incidence of defects (GD sample). Experiments with heat‐treated samples at 150 °C show a reduction in the number of spins which contributed to ESR signal for the GC sample. Considering data of thermogravimetry (TGA), X‐ray diffraction (XRD), and Mössbauer spectroscopy, the differences observed in ESR analysis are attributed to a magnetic mismatch in the AFM structure caused by the incidence of local defects, more common in GC sample. Results of heat‐treated samples are associated to an increase in the exchange interaction between grains, which reduces the number of mismatched spins and favors the AFM arrangement. Abstract : Goethite is an antiferromagnetic material but has a superimposed magnetic component, known as weak ferromagnetism. An investigation with different samples and technics is presented. It has been shown with ESR results that this component can be enhanced or suppressed when morphological and structural properties are changed by annealing or use of different synthesis route.